Letter to the Editor - Minute-by-minute monitoring of autoregulation - Sánchez-Porras, Renán; Santos, Edgar; Silos, Humberto; Sakowitz, Oliver (Journal of neurosurgery, 2014)
"Letter to the Editor. Minute-by-minute monitoring of autoregulation" published on Sept 2014 by American Association of Neurological Surgeons.